A délszláv állam felbomlásának folyamata, az átalakulás aktuális kérdései - Szávai, Ferenc (Közép-Európai Közlemények, 2008)
In Public International Law, state succession is defined according to the Vienna Convention of 1978 on succession of states in respect of treaties, and in the 1983 convention on succession in respect of state property, archives and debts. In succession to Soviet Union, Czech Republic and Yugoslavia the succession states took over on a percentage basis the common state property and debts as inheritance. Now carry on the dissolution of Yugoslavia by the secession of Kosovo. If have Kosovo province the right to self-determination? What will be influence for other independence aspiration? Is Serbia a gateway to the European Union? Accession of Serbia to the European Union depends on several factors.